Genotoksisite testlerinin yeni ilaç geliştirme sürecindeki önemi - BECEREN, AYFER (My University, 2018)
In the preclinic investigation period at the beginning of the drug development process, it is an obligation to subject candidate drugs to genotoxicty investigations. Genotoxicty data of drugs that are developed with these tests are demanded as a part of the security evaluation process by regulatory authorities in various countries. The demand of these laboring and costly data by regulatory authorities of various countries in different standards prevents potential candidate drugs from being marketed, interrupts the drug development process and causes unnecessary utilization of experimental materials in researches. Therefore, nowadays, it is generally accepted that the researches aimed at achieving these data are implemented with standardized approaches in the guidelines of international harmonisation organizations such as ICH (International Council for Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use) and OECD (Organisation for Economic Cooperation and Development). In this review, it is aimed to provide current information about the various genotoxicity tests which are used commonly in the drug development process, in accordance with ICH, OECD guidelines and literature.

İlaç geliştirme sürecinin başlangıcındaki preklinik araştırma döneminde, aday ilaçların genotoksisite testlerinden geçirilmesi bir zorunluluktur. Bu testlerle elde edilen genotoksisite verileri, çeşitli ülkelerdeki düzenleyici otoriteler tarafından güvenlilik değerlendirme sürecinin bir parçası olarak istenmektedir. Elde edilmesi oldukça zahmetli ve maliyetli olan bu bilgilerin, farklı ülkelerin düzenleyici otoriteleri tarafından değişik standartlarda istenmesi, potansiyel ilaç adaylarının pazarlamasını engellemekte, ilaç geliştirme sürecini kesintiye uğratmakta ve araştırmalarda gereksiz yere deney materyali kullanımına neden olmaktadır. Bu bakımdan, günümüzde bu bilgileri elde etmeyi amaçlayan araştırmaların, ICH (İnsanda Kullanılan İlaçların Ruhsatlandırılması İçin Teknik Gerekliliklerin Uyumlandırılması Uluslararası Birliği) ve OECD (Ekonomik Kalkınma ve İşbirliği Örgütü) gibi uluslararası harmonizasyon örgütlerinin kılavuzlarında standardize edilen yaklaşımlarla uygulanması genel kabul görmektedir. Bu derlemede, ilaç geliştirme sürecinde kullanılan genotoksisite testlerine ilişkin, ICH, OECD kılavuzları ve literatür ışığında güncel bilgiler verilmesi amaçlanmıştır.
The importance of genotoxicity tests in new drug development process
Keywords: reclinical drug evaluation; genotoxicity tests; DNA damage; international guidelines; Preklinik ilaç değerlendirmesi; genotoksisite testleri; DNA hasarı; uluslararası kılavuzlar